2011
DOI: 10.3109/08977194.2010.544656
|View full text |Cite
|
Sign up to set email alerts
|

Combined VEGF and LMP-1 delivery enhances osteoprogenitor cell differentiation and ectopic bone formation

Abstract: A novel strategy to enhance bone repair is to combine angiogenic factors and osteogenic factors. We combined vascular endothelial growth factor (VEGF) and LIM mineralization protein-1 (LMP-1) by using an internal ribosome entry site to link the genes within a single plasmid. We then evaluated the effects on osteoblastic differentiation in vitro and ectopic bone formation in vivo with a subcutaneously placed PLAGA scaffold loaded with a cloned mouse osteoprogenitor cell line, D1, transfected with plasmids conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…CADM1 has been recently identified as a marker of higher bone forming capacity of MSCs [40]. The findings of this study shed light on possible mechanism for our earlier findings that D1 cells transiently (≤1 week) expressing VEGF and BMP-6 genes [32] or VEGF and LMP-1 genes [33] induced significantly greater bone formation at week 3 than that induced by D1 cells alone or D1 cells expressing any single gene. It appears from our present study (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…CADM1 has been recently identified as a marker of higher bone forming capacity of MSCs [40]. The findings of this study shed light on possible mechanism for our earlier findings that D1 cells transiently (≤1 week) expressing VEGF and BMP-6 genes [32] or VEGF and LMP-1 genes [33] induced significantly greater bone formation at week 3 than that induced by D1 cells alone or D1 cells expressing any single gene. It appears from our present study (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…In the last decade several investigators have shown that exogenous addition MSCs, VEGF and BMP synergistically enhances bone formation but the exact mechanism remains elusive. It is difficult to explain this synergy through VEGF induced increased angiogenesis since our previous studies on synergistic aspect [32][33] revealed that increase in angiogenesis did not always correlate with increase in osteogenesis. While complete inhibition of angiogenesis is known to inhibit bone formation [3][4] the number of vessels and VEGF expression levels are reported to be similar in non-union fractures and fractures that heal [38][39].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The effectiveness of LMPs in inducing bone formation in vivo has been demonstrated, using different strategy to deliver the gene/peptide at the site where the bone healing was required (H.S. Lattanzi et al, 2008;Parrilla et al, 2010;Pola et al, 2004;Sangadala et al, 2009;Strohbach et al, 2008b;X. Wang et al, 2011;Yoon et al, 2004).…”
Section: Lim-mineralization Proteinsmentioning
confidence: 99%